2021
DOI: 10.3389/fnins.2021.637336
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review and Meta-Analysis of Autoantibodies for Diagnosis and Prognosis in Patients With Chronic Inflammatory Demyelinating Polyradiculoneuropathy

Abstract: Objectives: To review the available evidence on sensitivity and specificity of anti-NF155 antibody detection in diagnosing a specific subset of patients with chronic inflammatory demyelinating polyradiculoneuropathy (CIDP) and to calculate the frequencies of different autoantibodies to paranodal proteins.Background: Diagnosis of CIDP relies on clinical and neurophysiologic criteria and lacks useful diagnostic biomarkers. A subset of CIDP patients exhibit atypical clinical phenotypes and impaired response to co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(22 citation statements)
references
References 37 publications
1
21
0
Order By: Relevance
“…Previous case series and systematic reviews suggested that patients with anti-NF155+ AN respond poorly to IVIg or that IVIg response is less frequent than in seronegative CIDP. 3 , 30 , 31 , 33 This has been described in other IgG4-mediated diseases such as anti-muscle-specific tyrosine kinase-positive myasthenia gravis. 34 There are different hypotheses on why this happens in IgG4-mediated diseases, although none has been validated.…”
Section: Discussionmentioning
confidence: 80%
“…Previous case series and systematic reviews suggested that patients with anti-NF155+ AN respond poorly to IVIg or that IVIg response is less frequent than in seronegative CIDP. 3 , 30 , 31 , 33 This has been described in other IgG4-mediated diseases such as anti-muscle-specific tyrosine kinase-positive myasthenia gravis. 34 There are different hypotheses on why this happens in IgG4-mediated diseases, although none has been validated.…”
Section: Discussionmentioning
confidence: 80%
“…The standard treatment, considered an autoimmune origin of CIDP, is based on the administration of corticosteroids, immunoglobulins, plasma exchange and immunosuppressive therapy [ 6 ]. The subgroup of patients with disruption of axoglial junctions in the node/paranode region tends to show tremor, ataxia, cranial nerve involvement and poor response to intravenous immunoglobulin (IVIg) [ 19 , 51 , 52 , 53 ].…”
Section: Anatomymentioning
confidence: 99%
“…Patients without defined presence of antibodies (seronegative) CIDP respond to immunotherapy in 60–80% of cases, while as much as 80% of patients with nodal/paranodal antibodies have poor response to the therapy [ 50 , 52 ]. IVIg in seronegative CIDP patients might inhibit the complement pathway and modulate the Fc receptors on macrophages, promoting remyelination, although some data are contrary to this theory [ 54 ].…”
Section: Anatomymentioning
confidence: 99%
See 1 more Smart Citation
“…[5][6][7][8] Anticontactin (CNTN1) antibodies can be detected from 1% to 8% of CIDP and exceptionally seen in association with nephrotic syndrome. 9 To date, only 24 cases of association between CIDP and membranous nephropathy were reported. 1,3,4,10,11 We aim to describe an exceptional case of rituximab responsive relapsing-remitting anti-CNTN1 IgG4 CIDP associated with a nephrotic syndrome and to compare our observation with previously reported similar cases.…”
Section: Introductionmentioning
confidence: 99%